Anxiety, Depression, and Post-Traumatic Stress Disorder (PTSD) Symptomatology According to Gender in Health-Care Workers during the COVID-19 Pandemic in Peru Shortened Title: “Psychological Impact of the Pandemic on Women” - Martínez Pajuelo, Alex Ricardo (2022)
Objective: The current study will evaluate the association that the COVID-19 pandemic has had with health-care workers and identify the factors that influenced the female gender being more affected. Methods: This is a cross-sectional study conducted in two hospitals in Arequipa (a Peruvian city). The participants were health-care workers. We applied a questionnaire with sociodemographic information and three scales: the Generalized Anxiety Disorder-7, the Patient Health Questionnaire-9, and the Primary Care Post-Traumatic Stress Disorder (PTSD) Screen for DSM-5. The main outcomes were anxiety, depression, and PTSD scores. The exposure of interest was gender. The scores of the scales were estimated by medians and percentiles 25–75 (p25–p75), and we used linear regression to estimate the crude and adjusted coefficients and their respective confidence intervals at 95% (CI 95%). Results: There were 109 participants, and 43.1% were women. The anxiety, depression, and PTSD median (p25–p75) scores in the study population were 6 (2–11), 6 (2–10), and 1 (0–3), respectively. The adjusted analysis showed that the female sex had 4.48 (CI 95% 2.95–6.00), 4.50 (CI 95% 2.39–6.62), and 1.13 (CI 95% 0.50–1.76) higher points on average for the scales of anxiety, depression, and PTSD symptoms in comparison to males, respectively. Conclusions: Female health-care workers showed increased scores of mental health issues in comparison to male health-care workers.